PENDIDIKAN KEWIRAUSAHAAN BERBASIS POTENSI LOKAL: PENGOLAHAN RUMPUT LAUT MENJADI KERUPUK" - Jon A. Lalang Yame; Sunenti H Lanmai, Jordi L. Modena, Dela Dorkas Karma, Elisabet Laihman, Arlin N. Atalaka, Sufwinda B (JOURNAL OF COMMUNITY DEDICATION, 2025)
The KBPM Desa student work programme identifies the local food potential of Bana Village to be managed into food products with economic value. The main objective of this programme is to improve the community's skills in processing and packaging products, as well as opening up wider marketing access through digitalisation. Through training, discussions, and collaborative work, the community is encouraged to be more confident in developing the village's flagship product, namely seaweed crackers. Through the training and production process, participants gained skills in the production process and processing of seaweed into crackers, and showed high motivation to develop small businesses based on local potential. From a production perspective, participants were able to understand and carry out the process of processing seaweed into crackers that are ready for consumption. From a marketing perspective, participants began to realise the importance of promotional strategies, attractive packaging design, and the use of social media to expand market reach. Thus, this activity succeeded in increasing the understanding and entrepreneurial skills of the community and students, and proved that local resources (local potential) such as seaweed can be the basis for more valuable and useful food product innovations. This demonstrates that entrepreneurship education focused on local potential not only supports family economic growth but also contributes to the development of flagship products in Alor District.